2014
DOI: 10.1088/0953-8984/26/4/042201
|View full text |Cite
|
Sign up to set email alerts
|

AEMnSb2(AE=Sr, Ba): a new class of Dirac materials

Abstract: The Dirac fermions of Sb square net in AEMnSb2 (AE=Sr, Ba) are investigated by using first-principles calculation. BaMnSb2 contains Sb square net layers with a coincident stacking of Ba atoms, exhibiting Dirac fermion behavior. On the other hand, SrMnSb2 has a staggered stacking of Sr atoms with distorted zig-zag chains of Sb atoms. Application of hydrostatic pressure on the latter induces a structural change from a staggered to a coincident arrangement of AE ions accompanying a transition from insulator to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 16 publications
10
70
0
Order By: Relevance
“…Manganese (Mn) based pnictide compounds with MnP n (P n = P, As, Sb, and Bi) layers have been in the spotlight by virtue of their intriguing magnetic properties, most notably the recently discovered Dirac semimetals AMnP n 2 (A = Ca, Sr, and Ba) [1][2][3]. The quasi two-dimensional (2D) AMnP n 2 have been recognized as the three-dimensional (3D) analogs of the 2D graphene with linearly dispersing bands that cross at the Fermi energy [2]. Generally, the Mn atoms are arranged in a square lattice or in a slightly distorted orthorhombic lattice and undergo antiferromagnetic (AFM) ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese (Mn) based pnictide compounds with MnP n (P n = P, As, Sb, and Bi) layers have been in the spotlight by virtue of their intriguing magnetic properties, most notably the recently discovered Dirac semimetals AMnP n 2 (A = Ca, Sr, and Ba) [1][2][3]. The quasi two-dimensional (2D) AMnP n 2 have been recognized as the three-dimensional (3D) analogs of the 2D graphene with linearly dispersing bands that cross at the Fermi energy [2]. Generally, the Mn atoms are arranged in a square lattice or in a slightly distorted orthorhombic lattice and undergo antiferromagnetic (AFM) ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Such control can potentially be realized in materials in which magnetic order coexists with non-trivial electronic band topology. Recent ARPES, quantum oscillation, neutron diffraction and ab initio band structure studies suggest that materials in the AMnSb 2 (A = Ca, Sr, Ba, Eu, Yb) family display many of the required properties [9][10][11][12][13][14][15][16][17][18] . The two-dimensional zig-zag layer of Sb atoms [ Fig.…”
mentioning
confidence: 99%
“…ARPES measurements have provided direct evidence for the existence of strongly anisotropic Dirac cones in SrMnBi 2 and CaMnBi 2 [16]. And first-principles calculations of AMnSb 2 (A = Sr, Ba; replacing Bi with Sb) have indicated Dirac fermionic behavior could be realized in BaMnSb 2 [17]. Subsequent transport and magnetization measurements and relativistic first-principles calculations have suggested that BaMnSb 2 is a 3D WSM by virtue of weak ferromagnetism due to canted Mn moments in the antiferromagnetic (AFM) structure [18].…”
Section: Introductionmentioning
confidence: 99%